Technological Change, Organizational Change, and Job Turnover - Thomas K. Bauer; Stefan Bender (Institute for the Study of Labor (IZA), 2002)
This paper uses a German employer-employee matched panel data set to investigate the effect of organizational and technological changes on gross job and worker flows. The empirical results indicate that organizational change is skill-biased because it reduces predominantly net employment growth rates of unskilled and medium-skilled workers via higher job destruction and separation rates, whereas the employment patterns of skilled workers are not affected significantly. New information technologies do not have significant effects on gross job and worker flows as soon as establishment fixed-effects are controlled for.
Keywords: O33; J63; L23; 330; linked-employer-employee data set; information technology; organizational change; job turnover; worker turnover; Technischer Fortschritt; Organisatorischer Wandel; Arbeitsmobilität; Schätzung; Deutschland